Effects of temperature in reactive distillation of vapor from non-catalytic pentaerythritol tetradodecanoate (petd) reactor - Shahrulnizam, Jamen (2006)
Pentaerythritol Tetradodecanoate (PETD) is a new ester which used as varnish addictive in magnetic wire production. In many foreign countries, production of PETD has been conducted but in Malaysia, the technology of PETD production still not localized by any Malaysia company. The objective of this research is to study effects of temperature in non-catalytic PETD reactor. Method for experiment of this research is using reactive distillation as unit operation and six different temperatures from 180°C to 230°C will be manipulated. The products from the experiment has been analysed using Gas Chromatography (GC). Results show that at 200°C is an optimum temperature for non-catalyst PETD production. It may observe that at 200°C is the maximum reaction for this production of PETD. So, for best temperature for producing PETD using reactive distillation is at 200°C because at this temperature, there are maximum reaction and higher conversion for PETD. Outcome from this research can be considered as pioneer process in localizing the technology, scale up and commercialization of PETD production.